Successfully treated massive pulmonary thromboembolism and thrombus in the right atrium due to diffuse malignant lymphoma: a case report - Inoue, Hiromu; Yasu, Takanori; Kawahito, Koji; Kubo, Norifumi; Nishida, Junji; Kawakami, Masanobu; Saito, Muneyasu (Journal of cardiology, 2006)
A 40-year-old man presented with massive pulmonary embolism related to diffuse large B cell lymphoma. His hemodynamic state worsened rapidly to shock after sudden onset of dyspnea. Echocardiography and thoracic computed tomography indicated pulmonary thromboembolism due to deep venous thromboembolism, associated with a mass in the anterior mediastinum and a 5 x 8 cm mass in the left pelvis compressing the left femoral vein. He underwent emergent surgery to remove a huge thrombus from the right atrium through the bilateral pulmonary arteries. Soon after this surgery, his hemodynamic state recovered and excision of the left cervical lymph node revealed diffuse large B cell lymphoma. Venous compression by the lymphoma mass had caused hemostasis and thrombus formation in the present case.